Pengaruh Model Pembelajaran Crossword Puzzle Terhadap Hasil Belajar IPS Siswa Kelas IV SD - Khairunnisa, Indah; Idawati, Idawati; Muchtar, Fitri Yanty (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
Abstract. The aim of this research is to determine the effect of implementing the Crossword Puzzle learning model on social studies learning outcomes. The type of research is Pre-Experimental in the form of One Group Pretest-Posttest on 20 class IV students. The research instruments are tests, observation and documentation. Data analysis techniques are descriptive analysis and inferential analysis. The research results show that the average pretest value is 46.35 and posttest 81. Based on the results of the paired samples test hypothesis, the sig. (2-tailed) obtains 0.000 which indicates that 0.000<0.05 so (H0) is rejected and (H1) is accepted. Based on these results, it can be concluded that the crossword puzzle learning model influences the social studies learning outcomes of class IV students.